Biochemical, pharmacological, and toxicological attributes of caper (Capparis ovata) flowering buds and berries pickles. Issue 12 (30th July 2022) - Ozgun‐Acar, Ozden; Celik‐Turgut, Gurbet; Guner, Hüseyin; Sezer, Serdar; Sen, Alaattin
Abstract: Capparis ovata is a natural plant that grows widely in Turkey and its flowering buds and berry pickle are used in traditional medicine. Thus, the current study was expanded to evaluate the biochemical, pharmacological, and toxicological aspects of the Capparis ovata water extract (COWE). To determine the biochemical properties of COWE, mineral and fatty acid content, elemental analysis, flavonoid/phenolic content, radical‐scavenging capacity, and pesticide analysis were performed. Furthermore, to find out whether it had anti‐inflammatory properties, reverse transcription‐polymerase chain reaction (RT‐PCR) and nuclear factor kappa B (NF‐κB) luciferase activity tests were conducted. Whole‐genome transcriptomic profiling was carried out at a dose level of 500 mg/kg COWE to understand its pharmacological effect. Transaminases in serum were tested, and quantitative polymerase chain reaction (qPCR) was done using a custom design array that included the stress and molecular toxicology pathway to establish its toxicological qualities. As a result of the evaluations, it was observed that COWE has a high mineral and unsaturated fatty acid content, flavonoid/phenolic content, and radical‐scavenging ability. It significantly inhibited NF‐κB transcriptional activity as well as inflammatory cytokine expression in T‐lymphoblast cells. Whole‐genome transcriptomic profiling depicted that COWE modulates immune responses by upregulating natural killer cell activation, cellular response to type I interferon, B‐cell proliferation and differentiation, and Janus kinase–signal transducer and activator of transcription (JAK–STAT) pathways. Molecular Toxicology Pathfinder RT 2 Profiler PCR array analysis revealed that COWE at or lower dose of 500 mg/kg/day did not cause a comparatively adverse effect. According to the findings, COWE is a rich source of nutrients and can be used as an adjunct therapy for various inflammatory diseases. Abstract : The current study with detailed analyses strongly suggested that caper ( Capparis ovata ) is a rich source of nutrients and can be used as an adjunct therapy for various inflammatory and autoimmune diseases.